Effect of nano zero-valent iron (nZVI) on biohydrogen production in anaerobic fermentation of oil palm frond juice using Clostridium butyricum JKT37. (November 2021) - Arisht, Shalini Narayanan; Roslan, Rozieffa; Gie, Goh Ann; Mahmod, Safa Senan; Sajab, Mohd Shaiful; Lay, Chyi-How; Wu, Shu-Yii; Ding, Gong-Tao; Jamali, Nur Syakina; Jahim, Jamaliah Md; Abdul, Peer Mohamed
Abstract: Oil palm fronds (OPFs) are generally cast off as solid waste, which comprise of unused valuable product, fermentable sugars that can be utilised for biohydrogen generation. The OPF juice consisting of mainly glucose, sucrose, xylose, and fructose (TC = 51.53g/L) was utilised as a substrate for biohydrogen production using local strain, Clostridium butyricum JKT37 in batch anaerobic fermentation. The aim of this research was to optimise the initial pH and total carbohydrate (TC) concentration with the addition of nano zero-valent iron (nZVI) in OPF juice for enhanced biohydrogen yield (HY) and production rate (HPR). The optimal parameters obtained in this study were a pH of 6.5, 12.8 g/L TC, and 50 mg/L nZVI, which resulted in an optimum HY, HPR, and TC utilisation of 2.71 mol H2 /mol sugar, 88.75 mLH2 /LOPF h −1, and 88.28%, respectively. The optimised condition showed a 1.85-fold increase in hydrogen productivity as compared to the control (raw unadjusted OPF juice TC). The predominant acidogenic by-products were butyric, acetic, lactic, and formic acid. Although lactic acid is one of the major constituents of volatile fatty acids (VFAs), hydrogen production was feasible with the optimum level of factors. The HY and HPR improved by 45.39% and 85.20%, respectively, compared to fermentation of raw OPF juice. nZVI nanoparticle was used in this study as a catalyst in dark fermentation to improve biohydrogen production and accelerate the fermentation process. This study demonstrated that nZVI nanoparticle could effectively shorten the lag time and facilitated the hydrolysis and utilisation of OPFs. Graphical abstract: Image 1 Highlights: Biohydrogen was produced via mesophilic fermentation by Clostridium butyricum JKT37. Optimum parameters were pH of 6.5, TC of 12.8g/L and nZVI concentration of 50mg/L. 50 mg/L nZVI increases 46% of biohydrogen yield than positive control without nZVI. Maximum biohydrogen yield of 2.71 mol H2 /mol sugar obtained at optimum condition.